PENGARUH KETERLIBATAN PEMAKAI, KEMAMPUAN TEKNIK PERSONAL DAN UKURAN ORGANISASI TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI (SIA) PADA LEMBAGA PERKREDITAN DESA (LPD) DI KECAMATAN KUTA UTARA - Made Ananda Alvina Christy; Ni Luh Putu Sri Purnama Pradnyani; Luh Diah Citra Resmi Cahyadi (Faculty of Economics and Business, Universitas Warmadewa, 2023)
The Village Credit Institution (LPD) is a financial institution that specifically manages finances. Financial institutions like the LPD should be able to compete with other financial institutions with the help of an accounting information system. The information system used makes it easier for the public and customers to check balances, make transactions, withdraw money, and so on. The goal of this study is to find out how user participation, technical skills, and the size of an organization affect the performance of accounting information systems. This research was conducted at LPD in the North Kuta District. The population of this study were LPD employees in North Kuta District, and 80 samples were taken. Data analysis used multiple linear regressions. In this study, a quantitative research method was used, and the main data came from questionnaires with answers measured on a Likert scale. The population of this research is LPD employees in the North Kuta District. The sample determination method used was purposive sampling, and 80 respondents were taken as samples. Data analysis used multiple linear regression with SPSS 26-assisted data presentation. According to the research findings, user involvement has a positive and significant influence on accounting information system performance, personal technical skills have a positive and significant influence on accounting information system performance, and organizational size has a positive and significant influence on accounting information system performance. Researchers can make suggestions like getting accounting information system users more involved in making accounting information systems, giving accounting information system users training on a regular basis, and updating accounting information systems.